Financial obligations and economic barriers to antiretroviral therapy experienced by HIV-positive women who participated in a job-creation programme in northern Uganda. Issue 6 (2nd June 2016) - Dovel, Kathryn; Thomson, Kallie
Abstract: Economic costs are commonly cited as barriers to women's use of antiretroviral therapy (ART) in sub-Saharan Africa; however, little is known about how changes in women's income influence economic barriers to care. We analysed in-depth interviews with 17 HIV-positive women who participated in a job-creation programme in northern Uganda and two key informant interviews with programme staff to examine lingering economic barriers to care experienced after programme enrolment. We found that participants continued to experience economic barriers even after receiving a steady income and improving their economic status. Two themes emerged: first, limited resources in health facilities (e.g. drug and staff shortages) led participants to view ART utilisation as a primarily economic endeavour where clients made informal payments for prompter service or sought treatment in private facilities where ART was readily available; second, increased economic status among participants increased expectations of economic reciprocity among participants' social networks. Financial obligations often manifested themselves in the form of caring for additional dependents, limiting the resources women could allocate toward their HIV treatment. When paired with limited resources in health facilities, increased financial obligations perpetuated the economic barriers experienced by participants. Job-creation programmes should consider how health institutions interact with participants' financial obligations to influence women's access to HIV services.